Analisis Latar Belakang Pendidikan Hubungannya Dengan Kinerja Perangkat Desa Ononazara Kecamatan Tugala Oyo - Damai Natalia Lase; Syah Abadi Mendrofa; Palindungan Lahagu; Maria M. Bate'e (Visi Sosial Humaniora, 2024)
Analysis of Educational Background in its Relationship with the Performance of Ononazara Village Officials, Tugala Oyo District. Thesis. Management Study Program. Nias University. Advisor: Syah Abadi Mendrofa, S.E., M.M. According to Law Number 6 of 2014 concerning Villages, villages have the autonomy to manage governance and development, aiming to improve the welfare of the community. One critical element for implementing village autonomy is the competency of the village government apparatus. The village government, led by the village head and supported by officials, plays a key role in ensuring effective governance. However, observations in Ononazara Village, Tugala Oyo District, indicate that the performance of the village officials is still suboptimal. Issues such as the uneven educational background and varying levels of competence among officials lead to inefficiencies in carrying out their duties. This research aims to analyze the relationship between educational background and the performance of Ononazara Village officials. The focus is on the importance of education in enhancing performance, especially in the village governance sector. Data were collected through interviews with key informants and observations of the educational and performance conditions of the village officials. The findings reveal a significant correlation between educational background and performance, with officials who have higher education levels showing better performance in fulfilling their responsibilities. The study recommends improving education and training programs for village officials to enhance the overall performance of village governance.